The Role of Legal Aid Institutions in Providing Legal Education to Low Income Communities in Padang City - Fitri Fitri; M. Fachri Adnan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study was motivated by the low level of legal awareness and legal understanding among poor communities in Padang City, as well as the suboptimal implementation of legal counseling conducted by the Padang Legal Aid Institute (LBH Padang). These conditions have limited the ability of poor communities to access justice and legal assistance. The purpose of this study was to analyze the role of LBH Padang in implementing legal counseling for poor communities and to identify the factors influencing its implementation. This research employed a qualitative descriptive approach. Informants were selected purposively and consisted of LBH Padang officials, legal counselors, and community members who had participated in legal counseling activities. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing, while data validity was ensured through source triangulation. The findings indicate that LBH Padang has carried out its role in providing legal counseling by disseminating legal information, improving public understanding of legal rights and obligations, empowering communities, and facilitating access to legal aid services. However, the implementation of legal counseling still faces several challenges, including limited human resources, inadequate facilities and infrastructure, limited outreach coverage, and the low level of community participation and legal awareness. Therefore, stronger collaboration among LBH, the government, and the community is needed to improve the effectiveness of legal counseling and expand access to justice for poor communities in Padang City.